Emerging treatments for inflammatory bowel disease. (February 2020) - Hazel, Karl; O'Connor, Anthony
Inflammatory bowel disease (IBD), including Crohn's disease (CD) and ulcerative colitis (UC), is characterized by chronic inflammation, a relapsing and remitting clinical course, requirement for lifelong medication and often, significant morbidity. While multiple effective therapeutic options exist for the treatment of IBD, a proportion of patients will either fail to respond or lose response to therapy. Advances in therapeutics, such as the gut-specific anti-integrins, now offer patients an alternative option to systemic immunosuppression. Anti-interleukin 12 (anti-IL-12)/IL-23 agents offer new and effective treatment options for CD, while the oral small molecules now offer an oral alternative for the treatment of moderate-to-severe disease, previously requiring subcutaneous injection or intravenous infusion. Alternatives to pharmacological treatment such as stem-cell transplant and faecal microbiota transplant are also showing some promise in the treatment of both CD and UC.